A history of Canadian income tax. Volume 1, The Income War Tax Act, 1917-1948 - Campbell, Colin; Raizenne, Robert (Canadian Tax Foundation, 2022)
"Canada's first Income Tax was introduced in the Income War Tax Act of 1917. This book is the first to comprehensively analyze its design, why it was introduced, why a wartime measure was continued when the conflict was ended, and how the income tax grew into a principal aspect of the fiscal origins of the welfare state. It integrates an expert internal and technical history of the statute (definitions of income, tax rates and exemptions) with a broader overview of the political and economic histories which shaped the Income Tax Act's origins and development. Along the way the authors also look at a variety of related subjects, some not always included in tax histories - federal-provincial fiscal arrangements, tax evasion, tax administration, the way judicial decisions shaped the application of the Act, and tax treaties."– Provided by publisher
OCLC: 1291206973